THE IMPACT OF SOCIAL MEDIA ON CONSUMER BEHAVIOR - Kiki Farida Ferine; Silvy Sondari Gadzali; Abu Muna Almaududi Ausat; Marleni Marleni; Devy Mayang Sari (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
Social media has now become an increasingly important tool for all types of businesses. During the pandemic, one of the most successful social media campaigns was Stay-at-Home. This condition causes changes in consumer spending behavior in fulfilling life needs. This research aims to provide an analysis of the influence of social media on consumer behavior. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The findings of this study reveal that social media has changed consumer shopping behavior, especially during the pandemic. However, this behavior has become a post-covid-19 culture. This condition is of course a unique challenge for entrepreneurs to continue to innovate to develop modern products and services so that businesses survive and are able to continue to create consumer loyalty. It is hoped that this research will be an evaluation material for entrepreneurs if currently the business model has changed a lot, then it is time for them to change the old way to a new one by adopting social media and being flexible in improvising with modern marketing tools.